TRANSFORMASI PEMBELAJARAN EKONOMI MELALUI MEDIA DIGITAL - A.Ayu Astika; Nahda; Yuli Asmiranda; Sartina; Lia Vinky Ramadhani; Juliana; Irwani; Akila Fitri Annisa; Reva Zalina; Aprillah Alpianti; Irna Fitriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The digital era has driven significant changes across various sectors of life, including education, particularly in economics learning. This study aims to analyze the transformation of economics learning through the use of digital media by mapping current research trends, identifying the effectiveness of various digital learning tools, and examining the challenges and opportunities associated with their implementation. The study employs a systematic literature review method through the analysis of scientific journals and books published between 2021 and 2025. The data were synthesized from thirteen previous studies relevant to the theme of digital transformation in economics education. The findings indicate that digital media, such as Augmented Reality (AR), the instructional design platform Canva, and the local wisdom–based application Ekonara, contribute positively to improving learning outcomes, conceptual understanding, learning motivation, and students’ economic literacy. Beyond influencing instructional practices, digital transformation also requires a shift in educational paradigms, particularly in redefining teachers’ roles as learning facilitators, strengthening digital financial literacy, and addressing ethical considerations related to technology use. Therefore, the success of transforming economics learning depends not only on the utilization of technology but also on the balanced integration of technology, pedagogy, and learning content that is adaptive to the needs and characteristics of learners in the digital era.